Pricing uncertainty in wine markets following the Rudy Kurniawan scandal. (2nd January 2020) - Fougere, Emily; Kaplan, Erin K.; Collins, Courtney A.
ABSTRACT: This paper examines the impact of the Rudy Kurniawan fraudulent wine scandal on the market for wine sold at auction. Using data gathered from Wine Spectator's Auction Highlights reports, we estimate the difference in average price per lot of wine sold at auctions before and after Mr Kurniawan's arrest. We find a large statistically significant decrease (25–30%) in average price per lot following the arrest, with some evidence of even larger declines at Acker Merrall and Condit, the auction house most associated with the scandal.